The role of the Family Health Program in the organization of primary care in municipal health systems O papel do Programa Saúde da Família na organização da atenção primária em sistemas municipais de saúde - Maria Guadalupe Medina; Zulmira Maria de Araújo Hartz (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
The contribution of primary care to population health and health systems organization has been well documented, but some authors have highlighted that in Third World countries it has gained more ground in discourse than in facts and practices, with different possible configurations. The objectives of the current study were to evaluate and correlate organizational and local contextual characteristics to the degree of implementation of primary care in two municipalities (counties) in the State of Bahia State, Brazil, that had adopted the Family Health Program (FHP) as the system's central thrust. The research was based on two case studies with interwoven levels of analysis, using as the point of departure the underlying goal-image of primary care in the definition of criteria and standards for degree of implementation. The total scores for Municipalities A and B were 66 and 81, respectively (maximum total score = 100), while differences were observed between the urban and rural teams. The political and institutional contexts helped explain differences in the degree of implementation of primary care, but regardless of the municipal context, the study showed the emergence of organizational innovations closely related to the FHP. A contribuição da atenção primária à saúde das populações e na organização de sistemas de saúde é bem documentada, mas alguns autores têm destacado que, em países do Terceiro Mundo, ela ganhou mais força no espaço do discurso do que sobre fatos e práticas, com diferentes possibilidades de configuração. Este trabalho teve por objetivos avaliar e relacionar características organizacionais e do contexto municipal ao grau de implantação da atenção primária, em dois municípios da Bahia, Brasil, que adotaram o Programa Saúde da Família (PSF) como eixo estruturante do sistema. A pesquisa se realizou por meio de dois estudos de caso com níveis de análise imbricados, partindo de uma imagem-objetivo da atenção primária que orientou a construção de critérios e padrões do grau de implantação. Os escores totais dos municípios A e B foram, respectivamente, 66 e 81 (pontuação máxima de 100), observando-se igualmente diferenças entre equipes urbanas e rurais. Os contextos político-institucionais foram explicativos de diferenças no grau de implantação da atenção primária, mas, também, independente do contexto municipal, evidenciou-se a emergência de inovações organizacionais intimamente relacionadas ao PSF.